PTU-126 MR assessment of Crohn's related strictures correlates well with endoscopic findings facilitating safe and effective fluoroscopic dilatation. (28th May 2012) - Mohammed, N; Majeed, F; Tolan, D; Hyland, R; Hamlin, J
Abstract : Introduction: Intestinal strictures are a known complication of Crohn's disease (CD) and may be inflammatory (in part), fibrostenotic or post-operative (anastomotic). Treatment options include a combination of medical, endoscopic or surgical interventions. We performed a retrospective analysis of our radiological assessment and endoscopic management of CD related strictures. Methods: A retrospective review of adult patients who underwent balloon dilatation of CD related strictures by a single endoscopist at our institution. All patients underwent MR enterography prior to endoscopic assessment. Where necessary strictures were dilated under fluoroscopic screening. Endoscopic success was defined as the ability to traverse the stricture endoscopically after dilatation. Clinical success was defined as improvement in patients symptoms at follow-up. Complications, need for escalation of medical therapy, further dilatation or surgical intervention were recorded. Results: A total of 56 dilatations were performed in 30 patients (range 1–5). Mean age was 47.5 years. 16 were females. Mean duration of disease was 209 months (range 14–444). Mean follow-up was 29.5 months (range 1–135). 27/30 (90%) had at least one previous CD surgical resection (range 0–6, mean 1.96 per patient). The site of the strictures were ileo-colonic in 21/30 (70%), colonic 3/30 (10%), gastro-duodenal 3/30 (10%), ileo-rectal 2/30 (7%) and ileal pouch stricture in 1/30 (3%). Stricture lengths at MRE were 6 cm, a length deemed significant as this is the length of the colonoscopic balloons. At MRE 17 (57%) of strictures were deemed to have an inflammatory component and 13 (43%) fibrostenotic. There was correlation between MRE and endoscopic findings of the nature of the stricturing (inflammatory vs fibrostenotic) in 26/30 (87%) of cases. Fluoroscopic screening was used in 21/30 (70%) of cases. Dilatation endoscopically successful in 27/30 (90%) cases and clinically successful in 26/30 (87%) of cases. No dilatation was performed in one case due to technical difficulties and this patient ultimately required surgical resection. Fourteen patients (47%) required repeated dilatations for symptom recurrence (range 2–5 dilatations). 17 patients (57%) had an escalation of their medical therapy after dilatation. A total of 5/30 (17%) ultimately required elective surgery for symptom recurrence. Conclusion: MRE enterographic assessment of CD related strictures correlates well with endoscopic findings. Fluoroscopic screening facilitates safe and effective dilatation of CD related strictures which, together with optimising medical therapy, can reduce the need for surgical intervention. Competing interests: None declared.